2020
DOI: 10.3201/eid2603.190891
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of and Risk Factors for Latent Tuberculosis Infection among Prisoners, Tianjin, China

Abstract: T uberculosis (TB) remains a global threat to human health. In 2018, a total of 10 million cases of TB and 1.5 million deaths from TB were reported by the World Health Organization (WHO) (1). Globally, TB notification rates for prisoners are 11-81 times higher than those for local general populations (2). An estimated 10.4 million persons are held in penal institutions throughout the world, and each year the number of persons passing through prison gates could be 4-6 times higher because of high turnover of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
2
6
1
2
Order By: Relevance
“…Surprisingly the 61.6% prevalence of positive QFTP was much higher than the 13 and 20% prevalence in reported in Thai people living with HIV (PLWH) [ 13 ] and Thai health care workers, respectively [ 14 ] who were also tested by IGRA. Furthermore, this positive IGRA prevalence was higher than that reported from correctional facilities in other high TB burden countries such as China (52%) [ 15 ] and Ethiopia (51%) [ 16 ].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Surprisingly the 61.6% prevalence of positive QFTP was much higher than the 13 and 20% prevalence in reported in Thai people living with HIV (PLWH) [ 13 ] and Thai health care workers, respectively [ 14 ] who were also tested by IGRA. Furthermore, this positive IGRA prevalence was higher than that reported from correctional facilities in other high TB burden countries such as China (52%) [ 15 ] and Ethiopia (51%) [ 16 ].…”
Section: Discussionmentioning
confidence: 57%
“…Having been incarcerated ≥10 years, or having a previous incarceration were independent risk factors associated with LTBI prevalence in our study. Many previous studies have demonstrated that previous incarceration was a risk factor for LTBI in prisons, regardless of the TB burden in the country [ 15 , 17 , 20 , 32 ]. Furthermore, a longer duration of incarceration was associated with LTBI among Chinese [ 15 ] and Ethiopian [ 16 ] prisoners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of LTBI in the prison system is poorly understood; however, some studies have reported high rates of LTBI. This is the case for prisons in China, in 2016, with an LTBI rate above 50%, which is higher than that of the general population (13.5-24.3%), using an interferon-γ release assay (IGRA) 34 . From August 2018-November 2019, Gatechompol et al (2021) conducted a study in a maximum-security prison in Thailand, with 46.5% of patients testing positive for LTBI using tuberculin skin test (TST) and IGRA 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Tendencja do zachorowania wzrasta w grupach zwiększonego ryzyka i dotyczy to szczególnie bezdomnych, imigrantów i więźniów [6]. Więzienia, które są często nazywane rezerwuarami chorych na gruźlicę, stwarzają szczególnie duże zagrożenie dla zatrudnionych w aresztach i zakładach karnych, a także pośrednio dla społeczeństwa [7]. Więźniowie należą do grup wysokiego ryzyka oraz są na ogół biedni, mają niskie wykształcenie i pochodzą z grup ludności o niskim statusie ekonomiczno-społecznym, gdzie poziom zakażenia i przenoszenia gruźlicy jest wyższy.…”
Section: Omówienieunclassified